Frontline Allied Health Professionals in a Tertiary Children’s Hospital: Moving Forward Research Capacity, Culture and Engagement - Gimeno, Hortensia; Alderson, Lucy; Waite, Gillian; Chugh, Deepti; O’Connor, Graeme; Pepper, Lucy; Gibson, Faith; Wray, Jo; Sell, Debbie (International Journal of Practice-based Learning in Health and Social Care, 2021)
Higher levels of research activity within healthcare contexts are known to result in improvements to staff and patient satisfaction as well as treatment outcomes. In the United Kingdom (UK), clinical academic careers for Allied Health Professionals (AHPs) are a key priority development area. This article presents the results of a study that aimed to scope the research capacity of four AHP professions in a tertiary children’s hospital using the Research Capacity and Culture Tool. This tool captures individuals’ views of success or skill required for a number of research-related items within the three domains of individual, team and organisation. Response rate ranged between 45-71% across the four groups. Reported barriers to carrying out research included a lack of time, clinical work taking priority, and lack of suitable backfill (i.e., employing a therapist to cover the clinical post for the AHP to complete research activity). Motivators, on the other hand, included skill development, career advancement, and increased job satisfaction. As a first step to strengthen research skills, a systematic process was used to devise a suite of supportive strategies targeting the individuals’ perceived gaps in their research abilities across four pillars: (i) awareness, (ii) accessibility, (iii) opportunity and capacity, and (iv) knowledge and skills. This process drew on previously published accounts of successful research capacity and culture development, as well as the unique needs of staff at this tertiary children’s hospital. The outcome of this process was a structured framework to support research capacity, culture and engagement. The specific details of this framework are reported in this article together with further recommendations to promote research capacity, culture and engagement amongst AHPs.